Saturday

April 19, 2014

April 19, 2014

Posted by **Lars** on Thursday, May 27, 2010 at 8:20am.

- Math -
**PsyDAG**, Thursday, May 27, 2010 at 11:42amAssuming that you have no typos, add 9 and subtract 6x from both sides.

2/3x - 6x = 9

Multiply both sides by 3/2.

x - 9x = 27/2

-8x = 27/2

Divide both sides by -8.

x = -27/16

**Related Questions**

math - 3x-4=-2(3x+5) 3x-4=-2(3x+5) clear the fraction. 3x-4=-6x-10 add+6x+4 to ...

Math- Adv. Alg. w/ Trig. - I need help simplifying this expression: (3x^3y^5 + ...

Math - Can someone please check my answers below for accurateness? The ...

Algebra - checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4...

math - simplify (x^2-3x+6)-(36x^2-18x+6/6) (x^2-3x+6)-(6(6x^2-3x+1/6) cancel the...

math,help - Is this trinomial a perfect square x^2-6x+9 if the trinomial starts ...

Math - Differentiate g(x)=(x^3+1)(3x^2-1) so I use g'(x) X h(x) + g(x) X h'(x) ...

Math - How to rewrite an expression with negative exponents such as : -12(3x-1...

BobPursley..here it is: - Problem 1: (x-2)/(3x+4) - 6x/(x+1) What I did: Common ...

math - f(x)=-x^3+3x^2+9x-5 asked to find the stationary points this was my ...